Dynamics of Transcendence and Urbanism: The Latent Mechanisms of Everyday Religious Life and City Spaces. Issue 2 (15th March 2021) - Flint-Ashery, Shlomit; Stadler, Nurit
ABSTRACT: This paper examines the negotiated everyday experiences of Jewish Litvish people in London and Jerusalem, exploring ideas of transcendence and immanence in these spaces. By uncovering the relations between religious identity and boundary-making in urban settings, the paper exposes the latent social, organizational, and spatial mechanisms that determine communal demarcation lines in the everyday life of city spaces. We argue that to examine such processes, one must refer to the social system that drives local processes and the values that communities draw their strength from. Empirically, we compare the mechanisms the Haredi (strictly orthodox Jews) -Litvish communities in Jerusalem and London use to delineate areas between immanence and transcendence in city life. The findings point to planners' need to better understand how individuals cooperate and how community leaders are involved in developing urban structure.